The Effect of the Over Lapping Waves Strategy on the Collection of Mathematics among Students of the 5th Preparatory and the Development of Intelligent Thinking - Abdullah Kadhim, Raghad; Waleed Majeed, Balsam (International Journal of Psychosocial Rehabilitation, 2020)
The current era of rapid developments is an accelerating era of information in all areas of life; it was necessary to walk along and catch up and absorb this huge amount of information. Information literacy no longer fulfills the purpose, so the educators raiseded the slogan (11) "teach me how to learn" through the transition from traditional teaching methods to those based on the work of the mind of the learner and it’s the student should be a good thinker and acquire proper knowledge structures; his imagination leads him to assimilate information and extract and derive good information, and then to go into the preparation of curriculum and the search for positions that raise students thinking the researchers took upon themselves to carry out research and research related to thinking in order to produce conclusions and recommendations that support the idea of of activating the role of the student and came in the principles and standards which was issued by the national council for teaching mathematics (12, 13, 14, 15) In the United States, stressing the urgent need to help students see mathematics as a thought-provoking topic, as well as invitations to many seminars and conferences to develop appropriate solutions and care for the development of thinking and skills.